2013
DOI: 10.1038/nm.3197
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Flt3l is essential to mobilize dendritic cells and for T cell responses during Plasmodium infection

Abstract: Summary Innate sensing mechanisms trigger a variety of humoral and cellular events that are essential to adaptive immune responses. Here we describe an innate sensing pathway triggered by Plasmodium infection that regulates dendritic cell (DC) homeostasis and adaptive immunity via Flt3L release. Plasmodium-induced Flt3L release requires toll-like receptor activation and type I interferon production. We find that type I interferon supports the up-regulation of xanthine dehydrogenase, which metabolizes the xanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(143 citation statements)
references
References 61 publications
9
131
2
1
Order By: Relevance
“…Our results on CD8 + T cell activation confirm previous ex vivo data showing a superior efficiency of CD8 + DC at priming OT-I cells after exposure to transgenic PbA parasites expressing SIINFEKL (9). They are also consistent with in vivo studies showing a reduced number of activated endogenous CD8 + T cells after PbA infection of mice deficient in CD8 + DC (37,38,69). As CD8 + DC possess specialized machinery for cross-presentation (34), this likely underlies their unique capacity to prime CD8 + T cells during infection by Plasmodium species.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results on CD8 + T cell activation confirm previous ex vivo data showing a superior efficiency of CD8 + DC at priming OT-I cells after exposure to transgenic PbA parasites expressing SIINFEKL (9). They are also consistent with in vivo studies showing a reduced number of activated endogenous CD8 + T cells after PbA infection of mice deficient in CD8 + DC (37,38,69). As CD8 + DC possess specialized machinery for cross-presentation (34), this likely underlies their unique capacity to prime CD8 + T cells during infection by Plasmodium species.…”
Section: Discussionsupporting
confidence: 91%
“…Also, depletion of CD8 + DC in PbAinfected mice resulted in a sharp decrease in the numbers of activated endogenous CD8 + T cells in the spleen, and CD4 + T cell activation was also impaired (37). A similar result was obtained when CD8 + DC were depleted in P. chabaudi-infected mice (38). Another study analyzing CD4 + T cell responses to P. chabaudi Ag showed CD8 + DC as superior to CD8 2 DC at MHC II presentation in the steady-state, but the latter were more efficient during infection (39).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…It has recently been reported that the treatment of humanized mice with the haematopoietic cytokine Flt3L leads to an increase in human BDCA-1 + and BDCA-3 + DC subsets 36,38 Both, BDCA-1 + and BDCA-3 + DC produce IL-12 after Flt3L expansion in humanized mice. 36 We treated HIS mice when human haematopoietic reconstitution had reached plateau levels (12 weeks post …”
Section: 36mentioning
confidence: 99%
“…This approach is based on an accelerated dendritic cell (DC) coculture system, designed for the optimal activation of antigen‐specific T‐cells from PBMCs (Martinuzzi et al ., 2011). As circulating human DCs are rare, DC precursors within the starting PBMC material were mobilized using FLT3 ligand (FLT3L) (Breton et al ., 2015), known for its capacity to enhance the induction of T‐cell responses (Guermonprez et al ., 2013), and matured with a standard cocktail of inflammatory cytokines (TNF, IL‐1β, PGE2, and IL‐7).Furthermore, we focused on the priming of CD8 + T‐cells specific for the melanoma antigen Melan‐A/MART‐1, restricted by HLA‐A*0201 (HLA‐A2 from hereon). This specificity is particularly amenable to in vitro studies with limited volume blood samples due to naturally high precursor frequencies in the naive pool and the widespread occurrrence of HLA‐A2 in the general population.…”
Section: Introductionmentioning
confidence: 99%